Vitamin D deficiency is independently associated with mortality among critically ill patients (Clinics, 2015)
OBJECTIVE: Studies suggest an association between vitamin D deficiency and morbidity/mortality in critically ill patients. Several issues remain unexplained, including which vitamin D levels are related to morbidity and mortality and the relevance of vitamin D kinetics to clinical outcomes. We conducted this study to address the association of baseline vitamin D levels and vitamin D kinetics with morbidity and mortality in critically ill patients. METHOD: In 135 intensive care unit (ICU) patients, vitamin D was prospectively measured on admission and weekly until discharge from the ICU. The following outcomes of interest were analyzed: 28-day mortality, mechanical ventilation, length of stay, infection rate, and culture positivity. RESULTS: Mortality rates were higher among patients with vitamin D levels ;12 ng/mL) (32.2% vs. 13.2%), with an adjusted relative risk of 2.2 (95% CI 1.07-4.54; p< 0.05). There were no differences in the length of stay, ventilation requirements, infection rate, or culture positivity. CONCLUSIONS: This study suggests that low vitamin D levels on ICU admission are an independent risk factor for mortality in critically ill patients. Low vitamin D levels at ICU admission may have a causal relationship with mortality and may serve as an indicator for vitamin D replacement among critically ill patients.